Press (Latin America) - Vega Jiménez, Patricia (2014)
Jiménez, Patricia Vega: Press (Latin America) , in: 1914-1918-online. International Encyclopedia of the First World War, ed. by Ute Daniel, Peter Gatrell, Oliver Janz, Heather Jones, Jennifer Keene, Alan Kramer, and Bill Nasson, issued by Freie Universität Berlin, Berlin 2014-10-08. DOI: 10.15463/ie1418.10343.